The first representative of a new class of charge transfer complexes in o-quinone series for organic semiconductors. (June 2021) - Gusakov, E.A.; Demidov, O.P.; Tupaeva, I.O.; Vetrova, E.V.; Soldatov, M.A.; Tereshchenko, A.A.; Dubonosov, A.D.; Sayapin, Y.A.; Metelitsa, A.V.; Minkin, V.I.
Abstract: The first representative of a new class of charge transfer complexes for organic semiconductors was synthesized. The reaction of p -nitroaniline (PNA) with [1, 10]-phenanthroline-5, 6-dione (PD) results in the formation of a stable molecular charge transfer (CT) complex PNA3 -PD2 in a ratio of 3:2. The structure of the molecular CT complex PNA3 -PD2 was established by X-ray diffraction studies. Using the density functional theory method, it is shown that several types of intermolecular interactions are realized in the complex: between the PNA amino group and the nitro group of another PNA molecule, carbonyl groups, and PD nitrogen atoms. Complex PNA3 -PD2 is stable only in solid form. The diffuse reflectance UV–vis spectrum of PNA3 -PD2 crystal powder is characterized by the intense weakly structured long-wavelength absorption band up to 650 nm. Quantum chemical calculations of the electronic structure have shown that the complex PNA3 -PD2 is a straight-band semiconductor with a band gap of 2.11 eV. Graphical abstract: Image 1 Highlights: The first example of a new class of charge transfer complexes (CTC) in o -quinone series. The CTC is stable only in solid form and is a straight-band semiconductor. It has a structure PNA3 -PD2 (PNA, p -nitroaniline; PD, phenanthroline-5, 6-dione). X-ray and theoretical studies of the interactions in the layered structure of CTC. An effective approach to creating novel organic materials.